PENERAPAN METODE SIMPLE ADDITIVE SISTEM (SAW) PENDUKUNG KEPUTUSAN SELEKSI PENERIMA BEASISWA PADA SMK N 5 PADANG - Sahari Sahari; Syafri Arlis (Jurnal Teknologi Informasi dan Pendidikan, 2017)
In an institution or organization especially education, would be required a system to support the decision. There is a possibility decision system is also carried out concerned by the levels in the organization. The decision support systems application has designed to help the school management determine to select the students are eligible to receive a scholarship. That’s why using a decision support system admission scholarship at the Vocational High School 5 Padang using SAW (Simple Addiitive weighting) method. The method of calculation are going by manually first, then maded a computerized using a web-based application. With hoping this system is expected to reduce the occurrence of errors in the selection of students to get the scholarships of the schools proposed format. Keyword : Scholarship, Simple Addiitive weighting, Decision Support Systems